2019
DOI: 10.1002/prep.201900218
|View full text |Cite
|
Sign up to set email alerts
|

Bond Strain and Rotation Behaviors of Anharmonic Thermal Carriers in ‐RDX

Abstract: In this paper, we examine how bond strain and rotation carry heat in the molecular crystal α‐RDX. We calculate anharmonic lifetimes and then rank order the phonons and their distortions to the lattice by their importance as carriers of thermal energy. The motions of the atoms that constitute the strain and rotation are determined using the phonon mode energy and mode shapes under the harmonic approximation. To draw the distinction between propagating and diffusive carriers, we additionally compare the thermal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…However, similar values have precedents in disordered solids such as amorphous silicon, , SiGe alloys, lead halide perovskites, and so forth. This is ultimately indicative of the diffusive nature of the thermal carriers in complex molecular crystals such as RDX, as shown by Kumar et al , The high scattering rates of these low-frequency modes can be understood by investigating the type of scattering processes (absorption vs emission), as shown in Figure , and the strength of anharmonic coupling between the modes indicated by the Gruneisen parameter values and the number of 3-phonon scattering events indicated by the 3-phonon phase space volume, as shown in Figure . For the low-frequency modes (ω ϕ 1 ) in bands 1, 2, and 3, the majority of the scattering occurs via absorption processes involving two other low-frequency modes ω ϕ 2 and ω ϕ 3 .…”
Section: Resultsmentioning
confidence: 87%
See 1 more Smart Citation
“…However, similar values have precedents in disordered solids such as amorphous silicon, , SiGe alloys, lead halide perovskites, and so forth. This is ultimately indicative of the diffusive nature of the thermal carriers in complex molecular crystals such as RDX, as shown by Kumar et al , The high scattering rates of these low-frequency modes can be understood by investigating the type of scattering processes (absorption vs emission), as shown in Figure , and the strength of anharmonic coupling between the modes indicated by the Gruneisen parameter values and the number of 3-phonon scattering events indicated by the 3-phonon phase space volume, as shown in Figure . For the low-frequency modes (ω ϕ 1 ) in bands 1, 2, and 3, the majority of the scattering occurs via absorption processes involving two other low-frequency modes ω ϕ 2 and ω ϕ 3 .…”
Section: Resultsmentioning
confidence: 87%
“…Recently, however, estimates of thermal properties based on quasiparticle models have shown that a more complete representation of carriers in the Brillouin zone may be necessary for accurate modeling of phonon mechanisms. Kumar and co-workers showed that thermal conductivity of energetic crystals such as RDX can be dominated by nonacoustic carriers, which constitute the majority of the phonon modes, and that modes outside of the acoustic bands can contribute substantially to NN and other intramolecular bond distortions. , These observations suggest that the use of approximations that otherwise reduce the complexity of the rich set of optical modes in these materials may omit important contributions from a large number of modes to the transfer of vibrational energy.…”
Section: Introductionmentioning
confidence: 99%
“…The earlier calculations 69 , 70 based on PGM with three phonon scattering significantly underestimated the thermal conductivity; however, this is because PGM treats all phonons as propagating carriers while neglecting the diffusive nature of transport. However, we presently observe that the contribution of each mode to thermal conductivity is proportionally similar in both PGM (propagating carriers) and Allen–Feldman model 71 (diffusive carriers), as shown in Section S4 of the Supporting Information.…”
Section: Resultsmentioning
confidence: 92%
“…In the α-polymorph, the RDX ring takes on a chair conformation with two of the NO 2 groups pointed axially and the third NO 2 group oriented orthogonally along the equatorial direction , (other polymorphs are characterized by different NO 2 group orientations) with the crystalline unit cell qualitatively described as a quartet of dimers linked through adjacent N···O interactions. , Cleavage of an N–N bond and the production of various nitrogen-containing products (e.g., NO 2 , HNO, and HONO) have been observed from thermal and shock-excited samples and are thought be the first chemical steps in RDX initiation. Recent theoretical treatments by Chung and co-workers indicate that RDX is a highly anharmonic molecular crystal where excited, intramolecular vibrational modes rapidly scatter into low-frequency lattice modes . Indeed, several experimental and theoretical studies (refs for examples) have indicated anisotropic shock response in RDX, wherein it is hypothesized that select lattice distortions both couple strongly to high-frequency, “intramolecular” vibrations and cause increased heating due to irreversible mechanical deformation on preferential slip planes. ,, …”
Section: Introductionmentioning
confidence: 99%
“…However, such distinctions ultimately stem from the rigid molecule approximation, which assumes a clear frequency separation between intra- and intermolecular vibrations in a molecular crystal such that these modes can be decoupled by treating intermolecular vibrations after freezing the molecular internal degrees of freedom. While it is clear that the rigid molecule approximation fails to adequately describe EM behavior, ,, these termsand the qualitative description of displacements in a molecular crystalnonetheless serve as the foundational conceptual framework for discussing the vibrational structure of molecular crystals, and the distinction helps convey ideas pertaining to vibrational energy transfer. Indeed, “intramolecular” modes may span a few tens of molecules, and a clear distinction between RDX molecular vibrations and phonons or lattice vibrations appears to be inappropriate .…”
Section: Introductionmentioning
confidence: 99%